Effect of THD towards temperature properties of power conductor under harmonic influence - Muhammad Mokhzaini, Azizan (2007)
Power delivery system is having a great effect upon the existence of harmonic in power system. The ability of harmonic to influence some variable on power cable such as temperature and current has been a main issue regarding the safety of power cable as many electronic types of equipment are being introduced today, compared to .the past. They are nonlinear loads which tend to inject harmonic into whenever system they are in. Harmonic current tends to raise current magnitude into certain level and that adds extra burden of heat to the power cable. This paper investigated power loss component in a power cable, where an experiment designed to enable the component of harmonic being injected at will. The effect of THD towards temperature of the cable is analyzed and documented in form of graphical evidences. The pattern of current and temperature raise also taken into account and analyzed with great interest